2018
DOI: 10.1002/cbdv.201800398
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Antischistosomal Activities of Chalcones

Abstract: In this study, we evaluated the in vitro and in vivo schistosomicidal activities of chalcones against Schistosoma mansoni worms. In vitro assays revealed that chalcones 1 and 3 were the most active compounds, without affecting significantly mammalian cells. Confocal laser scanning microscopy and scanning electron microscopy studies revealed reduction on the numbers of tubercles and morphological alterations in the tegument of S. mansoni worms after in vitro incubation with chalcones 1 and 3. In a mouse model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Similar results were found for epiisopilosine, an alkaloid found in jaborandi ( Pilocarpus microphyllus ), which demonstrated reduction in the total number of worms when evaluated orally at a single dose of 400 mg/kg [21] . Also, some synthetic chalcones showed a reduction of about 32 % in the total number of worms after oral treatment with a single dose of 400 mg/kg [10] . However, according to literature, [22] considering the effectivity of an antischistosomal compound in vivo , only the active drugs that show worm burden reduction >80 % can be further characterized on mice bearing juvenile worms in the drug‐screening process.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were found for epiisopilosine, an alkaloid found in jaborandi ( Pilocarpus microphyllus ), which demonstrated reduction in the total number of worms when evaluated orally at a single dose of 400 mg/kg [21] . Also, some synthetic chalcones showed a reduction of about 32 % in the total number of worms after oral treatment with a single dose of 400 mg/kg [10] . However, according to literature, [22] considering the effectivity of an antischistosomal compound in vivo , only the active drugs that show worm burden reduction >80 % can be further characterized on mice bearing juvenile worms in the drug‐screening process.…”
Section: Resultssupporting
confidence: 76%
“…Additionally, the concerns over the emerging PZQ‐resistance development [6] have renewed interest in the search for new antischistosomal agents, particularly from natural sources [1,7,8] . Among natural compounds, chalcones have been shown promising antischistosomal activities [1,5,9,10] …”
Section: Introductionmentioning
confidence: 99%
“…An in vivo study with 2 ′ -Hydroxyflavanone showed that this flavonoid reduced the lesion size and L. amazonensis load in a murine model of cutaneous leishmaniasis [117]. Pereira et al stated the in vivo schistosomicidal activities of oral treatment with chalcones against Schistosoma mansoni worms, and the results showed that in mice there occurred a total worm reduction [118].…”
Section: Potential Of Dimeric Flavonoids As Antimicrobials: Form Lab ...mentioning
confidence: 99%
“…The schistosomicidal effect of two synthetic chalcones ( E -4’-hydroxychalcone and E -2’-hydroxy-4-methoxychalcone) was studied by Pereira et al. (2018) .…”
Section: Development Of E-ntpdases Inhibitorsmentioning
confidence: 99%